2020
DOI: 10.1186/s12906-020-02894-8
|View full text |Cite
|
Sign up to set email alerts
|

The risk of coronary artery disease in patients with rheumatoid arthritis using Chinese herbal products and conventional medicine in parallel: a population-based cohort study

Abstract: Background: Few studies have evaluated the association between the risk of coronary artery disease (CAD) and the use of Chinese herbal products (CHP) in patients with rheumatoid arthritis (RA). This study investigated the risk of CAD among patients with RA using CHP in combination with conventional medicine. Methods: A retrospective cohort study was conducted using the Taiwan National Insurance Research Database to assess 22,353 patients who had been newly diagnosed with RA between 1997 and 2010. Patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Various factors, including genetics, infections, environment, and immuno-inflammatory processes, have been implicated in the development of AS. [6][7][8][9] Currently, Western medicine treatment for AS mainly focuses on inflammation control and symptom reduction, utilizing nonsteroidal anti-inflammatory drugs (NSAIDs), biological agents, and immunosuppressants, [10][11][12] which have demonstrated not only immune-inflammation inhibition but also come with potential side effects. [13][14][15] Conversely, traditional Chinese medicine (TCM) has been increasingly utilized in AS treatment, offering unique advantages over Western medicine, such as fewer side effects, better prognosis, and significant improvements in AS symptoms and inflammation markers.…”
Section: Introductionmentioning
confidence: 99%
“…Various factors, including genetics, infections, environment, and immuno-inflammatory processes, have been implicated in the development of AS. [6][7][8][9] Currently, Western medicine treatment for AS mainly focuses on inflammation control and symptom reduction, utilizing nonsteroidal anti-inflammatory drugs (NSAIDs), biological agents, and immunosuppressants, [10][11][12] which have demonstrated not only immune-inflammation inhibition but also come with potential side effects. [13][14][15] Conversely, traditional Chinese medicine (TCM) has been increasingly utilized in AS treatment, offering unique advantages over Western medicine, such as fewer side effects, better prognosis, and significant improvements in AS symptoms and inflammation markers.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35] Recently, a number of statistical evidence and real world data have been accumulated to support the potential usefulness of IM for inflammatory and immunological improvement in patients with RA. [21,[36][37][38][39][40] For example, in a population-based cohort study in 2020, it was observed that the application of IM could lower the risk of coronary artery disease in RA. Additionally, in a more recent meta-analysis, it was reported that IM could attenuate the adverse effects of DMARDs.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in a more recent meta-analysis, it was reported that IM could attenuate the adverse effects of DMARDs. [36,39] Considering these circumstances, IM is expected to be worth investigating as a new treatment strategy that can lead to improved treatment results for RA.…”
Section: Introductionmentioning
confidence: 99%
“…East Asian herbal medicine (EAHM) could be a useful candidate for RA treatment that meets aforementioned objective. In East Asian nations such as China, Korea, and Japan, 500 to 1000 EAHM materials are commonly listed in pharmacopeia and are still actively utilized as medications for the treatment of rheumatic and musculoskeletal illnesses such [10–13] …”
Section: Introductionmentioning
confidence: 99%
“…In East Asian nations such as China, Korea, and Japan, 500 to 1000 EAHM materials are commonly listed in pharmacopeia and are still actively utilized as medications for the treatment of rheumatic and musculoskeletal illnesses such. [10][11][12][13] Based on previous study knowledge and challenge awareness, the authors set the following research objectives:…”
Section: Introductionmentioning
confidence: 99%